The Sad March to the Right: J. B. McLachlan's Resignation from the Communist Party of Canada, 1936 - Frank, David; Manley, John (Labour/Le Travailleur, 1992)
Abstract The resignation of J.B. McLachlan from the Communist Party of Canada in1936 is one of the more controversial episodes in the biography of a well-known Canadian labour radical. He was one of the few party leaders to enjoy wide recognition and popular support. His resignation was a difficult personal decision as well as a significant episode in the history of the party. In previous accounts his resignation has been presented alternately as a repudiation of labour radicalism generally and the Communist Party in particular, as a protest against the adoption of the united front in 1935, or as a form of local and personal political exceptionalism. McLachlan himself made no formal public announcement of his resignation and, except for an impromptu speech at a public meeting in September 1936, he remained largely silent. In response to a letter from party general secretary Tim Buck he prepared a personal explanation of his withdrawal from the party in June1936. This document, which is reproduced at the end of this article, remains the most important single piece of evidence concerning his resignation. An analysis of the circumstances leading to McLachlan's resignation shows that he did not regard his resignation as a repudiation of basic principles. He had supported the move towards the united front both internationally and domestically but disagreed with the implementation of the policy by the party leadership, especially as demonstrated in the case of the Amalgamated Mine Workers of Nova Scotia. McLachlan's view of the united front, which he considered to be consistent with the position of the Communist International, stressed the principles of internal democracy and local autonomy in the construction of the united front. In McLachlan's view there were already enough indications to show that leaders such as John L. Lewis had not been fundamentally transformed and that in the long run the decision to endorse an alliance of convenience with the established labour bureaucracy was an ambiguous legacy for the class struggle. In 1936 McLachlan was overtaken by events, but given his own history he was in a position to perceive the difficulties ahead more clearly than most of his contemporaries.